Israeli rejectionism a hidden agenda in the Middle East peace process - Amit, Zalman (Pluto Press, 2011)
"The Palestine-Israel conflict is one of the longest running and seemingly intractable confrontations in the modern world. This book delves deep into the 'peace process' to find out why so little progress has been made on the key issues. Zalman Amit and Daphna Levit find overwhelming evidence of Israel rejectionism as the main cause for the failure of peace. They demonstrate that the Israeli leadership has always been against a fairliy negotiated peace and hdave deliberately stalled negotiations for the last 80 years. The motivations behind this rejectionist position have changed, as have the circumstances of the conflict, biut the conclusion has remained consistent - peace has not been in the interest of the state of Israel. A fascinating read, and particularly timely as the Obama administration tries once more for a peace settlement, this book draw on a wealth of sources - including Hebrew documents and transcripts - to show that it is the Palestinians who lack a viable 'partner for peace'"--Publisher's description, p. [4] of cover.